A validation of Holland's occupation model by the smallest space analysis.[article]. - Magdalena, Federico V.
This study re-validated the hexagonal model of occupations developed by John L. Holland through use of Smallest Space Analysis, a technique which graphically shows a geometric structure in a body of data. The fit between theory and observation was determined by examining the "internal" and "external" aspects of the model. The application of SSA confirms, in varying degrees, the internal and external consistency of Holland's model. Results and discussion further shed light on the study's contribution in providing an independent line of evidence different from, although consistent with, previous attempts to verify Holland's occupation scheme.